SIMPLY MOTHERS: SHARED ELABORATION OF TECHNOLOGIES ON PRENATAL CARE OF VISUALLY IMPAIRED WOMEN - Geovana de Jesus Ferreira de Carvalho; Jheise Sandy da Cruz Tavares; Nayara Costa Modesto da Silva; Marcia Helena Machado Nascimento; Elizabeth Teixeira; Sílvia Teresa Carvalho de Araujo; Fernanda de Nazaré Almeida Costa (Universidade Federal do Paraná, 2023)
Objective: To develop educational technologies on prenatal care with and for visually impaired women. Method: A methodological study with a participatory interface and qualitative approach. It was carried out at a Specialized Technical Unit in the municipality of Belém, Pará, Brazil. Data production took place between August and September 2021 with six women. DOSVOX was used as a communication resource for the participants to answer four instruments with a view to developing the technologies. The analysis was of the thematic content type. Results: Women with visual impairment want respect for their autonomy, inclusion, and information from the professionals. The technologies produced point to the specific demands of visually impaired women and to the importance of preserving autonomy during prenatal care. Conclusion: Technologies produced in a participatory way point out women's specific perspectives and needs regarding prenatal care and may support both the nurses' actions in consultations and favor women with visual impairment during prenatal care.